SPATIAL SPILLOVER EFFECT OF CONFLICT ON FOOD SECURITY - Emehel, Adaora Nancy (Nazarbayev University School of Sciences and Humanities, 2024)
The objective of this research project is to examine the spatial spillover effects of conflicts on the food security of nations. Previous studies report negative consequences of conflict on neighboring states as well as those directly involved (Murdoch and Sandler 2002). Violent conflicts can have chain reactions on various aspects of society such as development (Gates 2012), security (Barnett, and Adger 2007), trade relations (Brück, and. De Groot 2013), and foreign direct investments (Ezeoha and Okereke Ugwu 2015). This study focuses on a relatively less theorized area of such spillover effects of conflict: food security. To examine a conflict’s negative impacts on food security, this study pays special attention to the two aspects of food security: food availability and food accessibility. Geographically, this project investigates the cases of Nigeria’s food security during the period of conflicts within Nigeria and in Cameroon, a bordering country. In particular, this study argues that the direct impact of a violent conflict is caused through psychologically affected behavior of food consumers in the region of conflict and damages on logistics of food supply. Indirect impacts are, on the other hand, explained by a sudden migration of refugee which brings consequences on both demand and supply sides of food market. This study employs the multiple case study research design, where 2-3 cases of violent conflicts are comparatively analyzed. Interviews serve as the primary method of data collection. This provides valuable insights into the experiences, perspectives, and consequences of the conflict in Cameroon on Nigeria's food security. Interviews are conducted with relevant stakeholders, including staff of non-governmental organizations, experts, and individuals affected by the violence and food crisis. The study uses process tracing as a method of data analysis. Applying process tracing would enable the identification and analysis of the causal mechanisms and routes through which the violence in one region affects the food security of another region. The findings of this study will integrate two bodies of literature, conflict studies and food security studies, as well as improve our understanding of the spatial diffusion effects of conflict on food security, specifically in Nigeria. The results derived from this study can guide policymakers and stakeholders in developing strategies and implementing measures to mitigate the adverse impacts of conflicts on food security.
Қақтығыстың АЗЫҚ ҚАУІПСІЗДІГІНЕ КЕҢІСТІК ТАРТЫЛУ ӘСЕРІ
ПРОСТРАНСТВЕННЫЙ ПЕРЕХОДНЫЙ ЭФФЕКТ КОНФЛИКТА НА ПРОДОВОЛЬСТВЕННУЮ БЕЗОПАСНОСТЬ
Keywords: Type of access: Embargo; Spatial Spillover Effects; Conflict Studies; Food Security Studies